Neuromechanical Integration of Pelvic-Thoracic Rotation among Youth Baseball Throwers - Winters, Eric; Doty, Steven; Lott, Melanie; Baker, James (Sports Medicine International Open, 2022)
The kinetic sequencing involved in the overhead throw anticipates an orchestration of body movement in which the more proximal segments of the body initiate movement prior to the more distal segment. This investigation explored neuromuscular and kinematic characteristics associated with one aspect of this kinetic sequencing, pelvic-to-thoracic rotation. Neuromuscular activation was recorded using surface electromyography and kinematic data was acquired using 3D videography. Specific objectives included 1) to describe the maximum angulation between the pelvic and thoracic body segments (Xmax angle), 2) to test the hypothesis that glove-side external oblique peak neuromuscular activation (GEOPA) occurs before Xmax angle, 3) to test the hypothesis that throwing-side external oblique peak neuromuscular activation (TEOPA) occurs following Xmax angle. Results show the mean Xmax angle to be 45.96 degrees (±10.83). The time of mean GEOPA (2.3653 sec±0.9094) occurred following the time of mean Xmax angle (2.2793 sec,±0.9026, p<0.01), thus refuting the first hypothesis. The time of mean TEOPA (2.3658 sec,±0.8978) occurred following the time of mean Xmax angle (2.2793 sec,±0.9026, p<0.01), thus confirming the second hypothesis. Results suggest that youth baseball participants may not adequately utilize the core of the body to fully benefit from the optimal kinetic sequencing postulated within the literature.
Keywords: Throwing; Neuromechanical; Thoracic Rotation; Kinetic Chain; Neuromuscular; baseball